Minat Belajar Siswa SMA Terhadap Pembelajaran Biologi Dengan Menggunakan Media Powerpoint - Jailan Sahil; Said Hasan; Ermin Ermin (Peneliti.net, 2023)
If students are interested in the subjects they are studying, they will understand the concept of biology that is being taught. Students' interest in learning is thought to be influenced by the use of instructional media, such as powerpoint-based subject matter. The purpose of this study is to ascertain whether class X students at SMAN 4 Ternate City are interested in studying biology. A questionnaire with 30 statement items that students filled out on a Google form is used in this type of research. Students' enjoyment, interest, and involvement in biology are all identified as indicators of interest in the questionnaire. The foundation of data analysis is the process of interpreting each student's questionnaire scores into very good, good, poor, and not good categories. The results of the study revealed that indicators of student enjoyment were 65.82 percent, student interest was 71.53 percent, attention was 72.21 percent, and involvement was 78.30 percent. According to the findings of this study, 71.97% of students have a moderate level of interest when using powerpoint media to participate in biology lessons. When the teacher shows and displays PowerPoint media and there are certain parts of the material that students do not understand, students will attempt to read repeatedly on biology material on PowerPoint media and ask the teacher if they do not. This is one of the very best indicators of student involvement in biology learning.